Landscape and Englishness - Burden, Robert; Kohl, Stephan (Spatial practices ;, 2006)
In the papers collected in this, the first volume of the Spatial Practices series, Englishness is reflected in the spaces it occupies or dwells in. Broadly influenced by a renewed and growing interest in questions of cultural identity, its emergence in Victorian theories and fictions of nationality, and the new cultural geography, the papers cover a rich variety of spaces and places which have been appropriated for cultural meanings: the rural countryside and farmland of the Home Counties in the early nineteenth century as Arcadian idyll in Cobbett, as the land to die for in war propaganda, an.